Omnibuslaw, Theory and Practice in the Field of Tourism Investment - Bendesa Gede Mas Indriyanigraha Arjaya; Anak Agung Ngurah Alit Wiraputra (Journal Equity of Law and Governance, 2025)
Execution is the implementation of a court decision that has permanent legal force (in krach van gwijsde) which is carried out by force against the losing party in a case who does not want to comply with the implementation of the court decision. As with the "word execution" which has been known especially in legal circles, it turns out that the word comes from English which in the original text is written excecutie which means to carry out, do, carry out, do, kill according to the judge's decision. Carrying out the death penalty in short, execution means carrying out or relating to the implementation of the executive institution, for example, which means an institution that has the authority to implement the Law. This process involves the assistance of court officials, including clerks and bailiffs, and can use general force such as the police or military if necessary. Execution aims to ensure the implementation of decisions that contain elements of punishment and must be carried out by paying attention to humanitarian values and justice. Law, as a tool to achieve social goals, has an important role in creating a more just and prosperous society, by accommodating public, social, and personal interests. In developing tourism in a region, it is necessary to pay attention to the potential of the region concerned. The more potential there is in an area, the more feasible the area is to be developed into a tourist destination so that the implementation of execution in tourist areas is very risky because it involves security forces. The implementation of execution involving security forces will affect the community and residents in tourist destinations that are widely visited by tourists, because it can affect the comfort and safety of tourists.